Psychological Problems of Online Learning to English as a Foreign Language During the Covid-19 Pandemic at Twelfth Grade Students of Senior High School Number 2 Muaro Jambi - Muhammad Ridzik Varedho; Yanti Ismiyati; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2023)
Main problem of this research are Covid-19 and Online learning that impact the learning process and psychological of EFL. The aim of this study is to determine how psychological issues related to the COVID-19 epidemic affect students who learn by online. The researcher will employ field research as the method of inquiry, observation and interviews. Research participants are 6 students who in twelfth grade. The findings lead to the psychological problems that indicated as Behavioural Apathy. Which are linked to the Cognitive psychology and Neuropsychology. Based on the findings, Students lost their interested in study by online learning, even lost their spirit in learning. Their feel so bored and tired, too much assignment and no explanation with bad signal (some of them) made theirs doesn’t really care about the lessons. The students being lazy to think and loves to be procrastinating of work. Some of them suffering by this situation but others not. The laziness of thinking and studying has persisted to this day.